Does the Meguma Terrane Extend into SW England? - Nance, R.; Neace, Erika; Braid, James; Murphy, Brendan; Dupuis, Nicolle; Shail, Robin (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
The peri-Gondwanan Meguma terrane of southern Nova Scotia, Canada, is the only major lithotectonic element of the northern Appalachian orogen that has no clear correlatives elsewhere in the Appalachians and lacks firm linkages to the Caledonide and Variscan orogens of western and southern Europe. This characteristic is in contrast with its immediate peri-Gondwanan neighbor, Avalonia, which has features in common with portions of Carolinia in the southern Appalachians and has been traced from the Rhenohercynian Zone of southern Britain eastward around the Bohemian Massif to the Carpathians and western Pontides. At issue is the tendency in Europe to assign all peri-Gondwanan terranes lying outboard of the Rheic suture to Avalonia, characterized by relatively juvenile basement and detrital zircon ages that include Mesoproterozoic populations, and those inboard of the suture to Cadomia, characterized by a more evolved basement and detrital zircon ages that match Paleoproterozoic and older sources in the West African craton. Although the unexposed basements of Avalonia and Meguma are thought to be isotopically very similar, the Meguma sedimentary cover contains scarce Mesoproterozoic zircon and is dominated instead by Neoproterozoic and Paleoproterozoic populations like those of Cadomia. Hence, felsic magma produced by crustal melting in the Meguma terrane (e.g. the ca. 370 Ma South Mountain Batholith) is isotopically more juvenile (εNd = –5 to –1, TDM = 1.3 Ga) than the rocks it intruded (εNd –12 to –7, TDM = 1.7 Ga). By contrast, felsic magma produced by crustal melting in Avalonia (εNd = –1 to +6, TDM = 0.7–1.2 Ga) is isotopically similar to its host rocks (εNd = –3 to +4, TDM = 0.9–1.4). The isotopic relationship shown by the Meguma terrane has also been recognized in the South Portuguese Zone of southern Spain, which is traditionally assigned to Avalonia. However, the Sierra Norte Batholith of the South Portuguese Zone (ca. 330 Ma; εNd = +1 to –3, TDM = 0.9–1.2 Ga) is on average more juvenile than the Late Devonian host rocks (εNd = –5 to –11) it intruded, suggesting instead an extension of the Meguma terrane into Europe. Available data for the Cornubian Batholith of SW England (ca. 275–295 Ma; εNd = –4 to –7, TDM = 1.3–1.8 Ga) and the Devonian- Carboniferous metasedimentary rocks it intruded (εNd = –8 to –11) suggests this may also be true of that part of the southern Britain (Rhenohercynian Zone) with which the South Portuguese Zone is traditionally correlated.